Nickel catalyzed regio- and stereoselective arylation and methylation of allenamides via coupling reactions. An experimental and computational study. Issue 22 (5th October 2018) - Liu, Yang; Cerveri, Alessandro; De Nisi, Assunta; Monari, Magda; Nieto Faza, Olalla; Lopez, Carlos Silva; Bandini, Marco
Abstract : A novel Ni-catalyzed regio- and stereoselective condensation of boronic acids/Me2 Zn to allenamides is documented and its potential explored. Abstract : The nickel catalyzed regio- and stereoselective condensation of boronic acids to allenamides is documented as a novel synthetic route to stereochemically defined tri-substituted enamides. The protocol has been implemented into a three-component variant intercepting the in situ formed allyl-Ni intermediate with a range of aldehydes. Additionally, evidence for the effective extension of this methodology to Me2 Zn is documented. Full rationale on the mechanism as well as its stereochemical outcome is provided by a synergistic experimental/computational approach.